2007
DOI: 10.1038/sj.ejhg.5201783
|View full text |Cite|
|
Sign up to set email alerts
|

Linkage and association analysis of CACNG3 in childhood absence epilepsy

Abstract: Childhood absence epilepsy (CAE) is an idiopathic generalised epilepsy characterised by absence seizures manifested by transitory loss of awareness with 2.5 -4 Hz spike -wave complexes on ictal EEG. A genetic component to aetiology is established but the mechanism of inheritance and the genes involved are not fully defined. Available evidence suggests that genes encoding brain expressed voltage-gated calcium channels, including CACNG3 on chromosome 16p12 -p13.1, may represent susceptibility loci for CAE. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 34 publications
0
34
0
1
Order By: Relevance
“…Homozygosity analysis of a consanguineous family exhibiting a high frequency of epilepsy, schizophrenia and/or hearing loss revealed a link to a region of chromosome 22 that includes the human stargazin gene (CACNG2) (Knight et al, 2008). The human γ-3 gene (CACNG3) on chromosome 16 has been implicated as a susceptibility locus in a subpopulation of patients suffering from childhood absence epilepsy (CAE) (Everett et al, 2007), whereas another study of consanguineous families showed that CACNG2 is not linked with CAE (Abouda et al, 2010). In a genetic study of families with a high incidence of schizophrenia, stargazin was linked to susceptibility in a subpopulation of patients (Liu et al, 2008).…”
Section: Tarps and Human Diseasementioning
confidence: 99%
“…Homozygosity analysis of a consanguineous family exhibiting a high frequency of epilepsy, schizophrenia and/or hearing loss revealed a link to a region of chromosome 22 that includes the human stargazin gene (CACNG2) (Knight et al, 2008). The human γ-3 gene (CACNG3) on chromosome 16 has been implicated as a susceptibility locus in a subpopulation of patients suffering from childhood absence epilepsy (CAE) (Everett et al, 2007), whereas another study of consanguineous families showed that CACNG2 is not linked with CAE (Abouda et al, 2010). In a genetic study of families with a high incidence of schizophrenia, stargazin was linked to susceptibility in a subpopulation of patients (Liu et al, 2008).…”
Section: Tarps and Human Diseasementioning
confidence: 99%
“…It is now recognized that mutations in the genes encoding the potassium channel KQT-like subfamily member 2 (Kv7.2) and member 3 (Kv7.3) are accountable for the BFNS pathophysiology. Indeed, the co-segregation of both chromosome 20q13.3 and 8q24 deletions and BNFS phenotype, has allowed the characterization of missense mutations of KCNQ2 (Kv7.2) and KCNQ3 (Kv7.3) as candidate genes of primary importance in BNFS etiology [95][96][97][98][99][100][101][102]. KCNQ2 and KCNQ3 mutations or duplications have been described in association to BNFS clinical features [103,104].…”
Section: Gene Mutations Voltage-and Ligand-gated Ion Channels and Epmentioning
confidence: 99%
“…CAE is highly genetic, and 16 -45% of patients have a positive family history (1). Mutations, polymorphisms, and variants associated with CAE have been identified in several genes encoding ion channels, including T-type calcium (2)(3)(4)(5), chloride (6), and GABA A receptor (7-9) channels.…”
Section: Childhood Absence Epilepsy (Cae)mentioning
confidence: 99%